UPAYA MENDORONG PENERAPAN DIGITALISASI PADA USAHA MIKRO DI DESA BENGKEL KABUPATEN SERDANG BEDAGAI - Hasriyati Hanum Siregar; Mustika Ayu Anggreini; Laiyinna Misqha Efendi; Annisa Ulul Azmi Panjaitan; Jodi Syahputra; khairina Tambunan (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2022)
This study intends to identify and analyze the challenges and obstacles to implementing digitization by MSMEs, especially micro-enterprises in Bengkel village, Serdang Bedagai district. This study uses a qualitative descriptive analysis technique by collecting secondary information and data from various sources and from previous journals that are linked to the digitalization of MSMEs. From the results of the research, information was obtained that the challenges and obstacles of micro and small businesses in implementing digitization returned to human resources who had low knowledge about digitization, low skills, experience, and low interest in micro-business actors in Bengkel village, Serdang Bedagai district to want to studying information and communication technology, apart from that the lack of access to supporting facilities and infrastructure is also an obstacle to the implementation of digitalization. Based on this, the authors suggest that the government through the cooperative and MSME services be more aggressive in optimizing the equitable application of digitalization, especially for the micro business sector in Bengkel village, Serdang Bedagai district, which in the end is useful for the micro businesses themselves so that they are able to survive and improve. productivity in this digital era.